HUBUNGAN ANTARA KARAKTERISTIK PERUSAHAAN DAN PENGUNGKAPAN SUKARELA ATAS LABA PROYEKSIAN DI BAWAH STANDAR AKUNTANSI KEUANGAN YANG BERBEDA - Arief Zulianto Susilo; Slamet Sugiri (Akademi Akuntansi YKPN Yogyakarta, 2012)
Previous studies find inconsistent results on the association between earnings volatility and firm value and voluntary disclosure of future earnings information. Those studies, however, do not take into account the different types of accounting standards. In fact, while many countries in the world have required firms listed in their stock exchanges to employ the IFRS (international financial reporting standards), some others have not required it until the year 2008. Do different accounting standards have impact on the association between those two firms’ characteristics (earnings volatility and firm value) and voluntary disclosure of future earnings information? We formally develop and empirically test hypotheses to answer the research question. We draw our samples from banking institutions listed in Indonesian Stock Exchange representing non-IFRS firms and and those listed in Australian Securities Exchange representing IFRS firms for the period of 2005-2008. Using interaction model, we find that different accounting standards do have significant influence on the association between earnings volatility and the voluntary disclosure of forward-looking earnings information. We, however, fail to find a significant effect of the different accounting standards on the association between firm value and the voluntary disclosure of future earnings information. The failure might suggest that, in the context of measurement perspective, the IFRS is actually indifferent from the non-IFRS.Keywords: Voluntary disclosures, forward-looking earnings information, firm value, earnings volatility, accounting standards